West Nile Encephalitis, an Unusual Infection in a Chronic Lymphocytic Leukemia Patient - Manuel R. Espinoza-Gutarra; Sherri L. Cervantez; Zohra Nooruddin (Case Reports in Hematology)
CNS involvement by CLL is a rare occurrence, usually happening in the context of a transformation to a more aggressive lymphoma in what is known as Richter’s transformation. We report a patient with active CLL who developed confusion and was found to have West Nile encephalitis that initially mimicked CNS involvement by CLL. The patient recovered with supportive treatment and later restarted ibrutinib therapy. This case illustrates the importance of maintaining a broad differential among cancer patients with new onset confusion as well as that of questioning malignant infiltration of CNS when there is concomitant active CNS infection.